Tetrapod Placement Structure for River Estuary Stability on Luk Ulo Jetty - Habsari, Gema Putri; Hadiyani, Rr. Rintis; Solichin, Solichin (Sustainable Civil Building Management and Engineering Journal, 2024)
The meeting between the river and the sea is called the estuary which is a vital environment for the reproduction of marine life, especially fish. The estuary is preferred for industrial and commercial activities, including the construction of a lucrative port due to easy access to sea transport. However, estuaries face challenges such as sediment deposition that leads to shallow channels and river estuary closures. The mouth of the Luk Ulo River in Kebumen Regency, Indonesia, is particularly affected by sediment transport from the coast and changing the flow of the river to shrimp farming areas. To overcome this problem, the construction of a jetty is planned to stabilize the estuary. The study focused on the Luk Ulo River Estuary, utilizing wave, tidal, and bathymetric data to plan jetties effectively, emphasizing on the proper arrangement of tetrapods to prevent estuaries from becoming unstable. The research, which uses a quantitative descriptive approach, aims to determine the needs of tetrapods, porosity values, and the protective arrangement of jetties. The findings show that the Luk Ulo River estuary, which has a wave-dominated morphological characteristic, is susceptible to estuary closure due to sediment transport dynamics. Data analysis provides insights into tides, sediment transport, tetrapod placement and tetrapod needs that are highly beneficial for future projects, facilitating the design of effective jetty construction measures. This research contributes valuable information to coastal planning, especially in the regular arrangement of tetrapods and the need for tetrapods.